MSMEs Tax Behavior and Voluntary Tax Compliance: The Role of Adaptive E-Filing and Tax Literacy - Duryana Duryana; Ekea Multi Febriyanti; Yusri Karmila (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: This gap is particularly evident in Indonesia, where MSMEs operate in the informal sector and have limited awareness of tax regulations. E-filing was introduced to simplify the tax reporting process and improve compliance, but its effectiveness is often hampered by a lack of tax literacy among MSMEs.Purpose: The objectives of this study are 1) to determine whether adaptive e-filing synergy affects voluntary tax compliance; 2) to determine whether tax literacy affects voluntary tax compliance; 3) to determine whether the tax behavior of MSMEs moderates the relationship between the influence of adaptive e-filing synergy on voluntary tax compliance; 4) to determine whether the tax behavior of MSMEs moderates the relationship between the influence of tax literacy on voluntary tax compliance.Design/methodology/approach: This is a quantitative study conducted in South Sulawesi Province, including Makassar City and the districts of Gowa, Takalar, Bulukumba, and Maros. The population in this study is unknown, with a sample of 110 MSMEs. Data analysis was performed using Structural Equation Modeling (SEM).Findings/Result: This study shows that adaptive e-filing synergy acts as a technological factor that significantly increases voluntary tax compliance among MSMEs by reducing administrative barriers, increasing efficiency, and improving perceptions of ease in tax reporting. Tax literacy also positively influences voluntary tax compliance by enhancing taxpayers’ understanding and awareness, although its influence does not fully guarantee consistent behavior without the support of motivational factors and system convenience. In addition, MSME tax behavior has been shown to strengthen the relationship between adaptive e-filing synergy and voluntary tax compliance, indicating that good tax behavior can transform technological benefits into actual compliance actions. Conversely, MSME tax behavior moderates the relationship between tax literacy and voluntary compliance in a negative and insignificant direction, indicating that tax knowledge is not yet strong enough to influence compliance without the support of practical experience, system convenience, and business conditions. Conclusion: Improving voluntary tax compliance among MSMEs is more effectively achieved through the integration of adaptive tax technology utilization and the formation of positive tax behavior, while tax literacy plays a supporting role in building compliance awareness.Originality/value (State of the art): This study highlights the need for an adaptive e-filing system that aligns with MSMEs’ levels of tax literacy and understanding. The findings of this study provide more holistic and effective policy recommendations for the government to improve MSME tax compliance, not only from a technological perspective but also from an educational perspective. Keywords: adaptive e-filing synergy, voluntary tax compliance, tax literacy, msme tax behavior